PERBEDAAN HASIL BELAJAR KELAS XII BAHASA DENGAN XII IPA DALAM BELAJAR BAHASA JEPANG DI SMA NEGERI 12 SEMARANG (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2018)
According to the result of this study, there is average result of Japanese mid-term test that explained 3rd grader of language (63,57%) is lower than 3rd grader of science (78,86%). Futhermore, there are internal fact included physical condition which the 3rd grader of language class (73,22%) and 3rd grader of science class had (83,34%). Then how many student got pay attention in the explanation of their Japanese teacher is (71,43%) for 3rd grader of language and (84,22%) for 3rd grader of science. Percentage who had joined Japanese language class is (68,75%) for 3rd grader of language class and (78,95%) for 3rd grader of science class. In addition, there are external fact that conduct the difference result of Japanese too, like how many student that had doing their homework there is (75%) for thr 3rd grader of language and (85,85%) for the 3rd grader of science and how it does school setup the class facility there is (78,58%) for 3rd grader of language and (88,82%) for 3rd grader of science.